Desenvolvimento e caracterização de partículas à base de biopolímeros e vinhaça com adição de biomassa microalgal para uso como fertilizante - Bettani, Silvia Raquel (Universidade Federal de São Carlos, 2018)
Sugarcane vinasse is the main wastewater from the ethanol industry, produced in a proportion of about 12 liters per liter of ethanol. Among alternatives to its disposal, Fertirrigation is commonly used in order to improve soil fertility of crops near the sugarcane producing areas. However, it is currently being questioned due to its effects on the soil and on groundwaters, caused by nutrient lixiviation. An alternative would be the development of slow and/or controlled release systems based on biodegradable polymers, such as pectin and chitosan, using vinasse as the solvent. This could reduce the amount applied and allow the extension of fertirrigation covered area. This study proposed the development of pectin and chitosan particles by ionotropic gelation using vinasse as solvent, intending a possible application in agriculture. Besides the use of vinasse, the incorporation of Desmodesmus subspicatus defatted biomass was considered to enhance nutrient content. The particles were evaluated according to their visual aspects, average diameter, moisture content, pH, solubility in water and CaCl2 0.01 mol L-1, mechanical property, chemical composition, morphology and biodegradation in soil. In general, the particles showed homogeneous matrix and spherical shapes. Pectin/vinasse particles had an average diameter of 2.7 mm, moisture content of 16.0%, pH 3.0, soluble matter of 64 and 48 g 100 g-1 in water and CaCl2 0.01 mol L-1, respectively, and compression force of 31 N. Chitosan/vinasse particles had an average diameter of 1.9 mm, moisture content of 15.2%, pH 6.6, soluble matter 43 and 34 g 100 g-1 in water and 0.01 mol L-1 CaCl2, respectively, and compression force of 62 N. The addition of microalgae biomass did not greatly affect particles properties. However, it increased the concentration of N for pectin particles and the concentration of micronutrients for both particles. The developed materials were able to retain nutrients from vinasse and showed, as solid particles, 65-93% of mineralization after 36 days of contact with soil. According to the Brazilian current legislation, they can be classified as biofertilizers and represent a novel application in agriculture, allowing the recycling of nutrients from vinasse, biopolymers and microalgal biomass to the soil.
Development and characterization of biopolymers and vinasse based particles added with microalgae biomass for use as fertilizer
Keywords: Pectina; Quitosana; Desmodesmus subspicatus; Vinhaça; Biopolímero; Pectin; Chitosan; Vinasse; Biopolymer; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA